2017
DOI: 10.1519/jsc.0000000000001590
|View full text |Cite
|
Sign up to set email alerts
|

Acute Responses to Resistance and High-Intensity Interval Training in Early Adolescents

Abstract: Harris, NK, Dulson, DK, Logan, GRM, Warbrick, IB, Merien, FLR, and Lubans, DR. Acute responses to resistance and high-intensity interval training in early adolescents. J Strength Cond Res 31(5): 1177-1186, 2017-The purpose of this study was to compare the acute physiological responses within and between resistance training (RT) and high-intensity interval training (HIIT) matched for time and with comparable effort, in a school setting. Seventeen early adolescents (12.9 ± 0.3 years) performed both RT (2-5 repet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 37 publications
5
20
0
Order By: Relevance
“…The progressive increase in HR throughout our INT protocol was consistent with other reports that examined the acute physiological responses to different modes of resistance exercise in youth [14,15,20]. During a 10-min bout of medicine ball interval training (30 s/exercise and 30 s rest/set) researchers reported that mean HR values during work sets ranged from 121.5 ± 12.3 bpm (61.1% HR peak) to 178.3 ± 9.4 bpm (89.6% HR peak) [14].…”
Section: Discussionsupporting
confidence: 90%
“…The progressive increase in HR throughout our INT protocol was consistent with other reports that examined the acute physiological responses to different modes of resistance exercise in youth [14,15,20]. During a 10-min bout of medicine ball interval training (30 s/exercise and 30 s rest/set) researchers reported that mean HR values during work sets ranged from 121.5 ± 12.3 bpm (61.1% HR peak) to 178.3 ± 9.4 bpm (89.6% HR peak) [14].…”
Section: Discussionsupporting
confidence: 90%
“…Obesity continues to rise [1, [2][3][4][5][6][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and the causes of this disease must be identified in hopes of a lifetime cure. Once the causes such as food allergens are eliminated, this disease can be reversed with interdisciplinary protocols.…”
Section: Discussionmentioning
confidence: 99%
“…While food allergy testing and elimination have been studied for reduction of migraine headaches [7,8] and intestinal disorders [9,10], the research has not been extensive in determining the efficacy of food allergy elimination in obesity reduction. Many weight loss protocols have been examined [4, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]26,27] but only a few studies have investigated identifying and eliminating the causes of obesity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations